46.1k views
4 votes
Olve each equation for the
1) -27 + m = 3m + 9

User Zenia
by
5.1k points

2 Answers

7 votes

-27 + m = 3m + 9

move +m to the other side

side changes from +m to -m

-27+m-m= 3m-m+9 ( combine like terms)

-27= 3m-m+9

-27= 2m+9

move +9 to the other side

-27-9= 2m+9-9

-27-9= 2m

-36=2m

divide both sides by 2 to get m by itself

-36/2= 2m/2

Cross out 2 and 2, divide by 2 and then becomes 1*1*m= m

divide -36/2 by dividing by 2

-36/2= -18

2/2= 1

m= -18

Check answer by using substitution method

-27 + m = 3m + 9

-27+-18= 3(-18)+9

-27-18= -54+9

-45= -45

Answer:

m= -18

User Individualtermite
by
5.2k points
6 votes

Hey!

------------------------------------------------

Steps To Solve:

-27 + m = 3m + 9

~Subtract m to both sides

-27 + m - m = 3m + 9 - m

~Simplify

-27 = 2m + 9

~Subtract 9 to both sides

-27 - 9 = 2m + 9 - 9

~Simplify

-36 = 2m

~Divide 2 to both sides

-36/2 = 2m/2

~Simplify

-18 = m

------------------------------------------------

Answer:

m = -18

------------------------------------------------

Hope This Helped! Good Luck!

User MarkE
by
5.1k points